Opportunities for a low-emission transformation of Ghana’s food systems - Bohne, S.; Martius, C.; Pingault, N. (CIFOR-ICRAF, 2026)
Ghana’s food systems contribute significantly (54.1%) to total national anthropogenic greenhouse gas (GHG) emissions – much above the global average (31%). The three primary sources of food system emissions in Ghana, ranked by decreasing order of importance, are: (i) land-use change emissions from deforestation, accounting for 40.7% of total food system emissions; (ii) farm gate emissions from livestock management (21.8%); and (iii) beyond-farm gate emissions from wastewater treatment and discharge (17.2%). While land-use change, livestock management, and waste dominate Ghana’s food system emissions, the most effective mitigation strategies emerge from considering both the origin and size of these emissions, as well as where Ghana can most rapidly and realistically implement change. The proposed priority measures therefore integrate emission magnitude with technical, economic, and institutional feasibility, consistent with Ghana’s Nationally Determined Contribution to the United Nations Framework Convention on Climate Change (UNFCCC) and Ghana’s food security and development priorities. Priority mitigation actions comprise intensifying cocoa production through agroforestry and strengthening preparedness for the EU Deforestation Regulation; improving fire management through controlled early burning and firebreak systems; reducing livestock emissions by boosting productivity and animal health; investing in urban (solid and water) waste management; diversifying into legumes and aquaculture to reduce dependence on meat for protein intake; actively integrating food system mitigation with improved market access and development; and increasing forest-related carbon sinks.